Determination Of The Same Leading Sectors In Blitar City - Satrianto, Alpon; Sasongko, Budi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
The purpose of this study was to determine the same leading sector based on the Klassen Typology method, Location Quotient, Shift-Share, Growth Ratio Models and Overlay. This study was based on the fact that most of previous studies only determined the leading sectors based on one method only and none of them determined which sectors categorized similar. Therefore, it is important to determine superior sectors from several methods and which sectors must be prioritized in the development. The data of this study were derived from the average GRDP of Blitar City on the basis of constant prices in 2010 according to business fields from 2011-2017. The results of this study conclude that the same leading sectors based on these 5 methods in Blitar City are 1) Large and Retail Trade; Car and Motorcycle Repair, 2) Information and Communication, and 3) Financial and Insurance Services. Therefore, the Blitar City government must continue to develop these sectors by increasing investment and ease of licensing so that the sectors can continue to increase its contribution to the economy of Blitar City.